(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the key themes in the literary works about postcolonialism is a critical framework that seeks to understand and analyze the impact of colonial rule on both the colonized and the colonizer. This article explores the significance of postcolonialism in English literature, highlighting its themes, key authors, and the transformation it has brought to literary narratives.